2023
DOI: 10.3233/wor-211318
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and its health and occupational determinants among hospital-based nurses during the COVID-19 pandemic

Abstract: BACKGROUND: Nurses worldwide were exposed to increased levels of occupational stress during the COVID-19 pandemic which could have hindered their level of health-related quality of life (HRQoL). OBJECTIVES: This project investigated HRQoL level in nurses during the COVID-19 pandemic and its health and occupational predictors. METHODS: A cross-sectional design was adopted and targeted full-time nurses in Jordan. Study collected data included demographics, 12-item Short Form health survey (SF-12) to measure HRQo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 48 publications
1
5
1
1
Order By: Relevance
“…Overall, a decreased quality of life was reported by more than three quarters of the patient-related professions. Almhdawi et al identified sleep quality, mental health, musculoskeletal health status, and financial status as potential influencing factors in relation to decreased quality of life among nurses during the COVID-19 pandemic [49]. In our study, more than one-third of patient-related professions were taking medications for musculoskeletal complaints.…”
Section: Patient-related Professionsmentioning
confidence: 56%
“…Overall, a decreased quality of life was reported by more than three quarters of the patient-related professions. Almhdawi et al identified sleep quality, mental health, musculoskeletal health status, and financial status as potential influencing factors in relation to decreased quality of life among nurses during the COVID-19 pandemic [49]. In our study, more than one-third of patient-related professions were taking medications for musculoskeletal complaints.…”
Section: Patient-related Professionsmentioning
confidence: 56%
“…The study found that nurses who reported better sleep quality self-assessments tended to have higher HRQoL levels. In contrast, increased levels of depression, musculoskeletal pain, and financial burden on their families were associated with lower HRQoL levels among Jordanian nurses [35] .…”
Section: Discussion and Resultsmentioning
confidence: 77%
“…In a study of the quality of life of nurses during the COVID-19 pandemic by Almhdawi KA. et al [6], the questionnaire was completed by 245 nurses. Using the NMQ questionnaire, they obtained the results: 75.5% of the participants had low back pain, 52.7% of the participants had neck pain, and 49% complained most about knee pain.…”
Section: Discussionmentioning
confidence: 99%
“…The NMQ questionnaire was used by Sharan D. et al [5] when examining pain in 350 physiotherapists. In the study by Almhdawi KA et al [6] the NMQ scale was used to assess musculoskeletal complaints among nurses during the COVID-19 pandemic in Jordan. The questionnaire is also widely used in research conducted in Poland.…”
mentioning
confidence: 99%